Statistics in Criminal Justice - Weisburd, David; Britt, Chester (Springer, 2014)
For the student of statistics, a textbook is like a train ticket. Not only does it provide a pass the student can use for entering a new and useful area of study; it also deﬁnes the route that will be taken and the goals that are important to achieve. Different textbooks take different approaches and emphasize different types of material.
Keywords: Criminal statistics; Criminology